2015
DOI: 10.1111/tan.12515
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of HLA‐A, ‐B, ‐Cw and DRB1 antigens in Moroccan patients with ankylosing spondylitis and a comparison of clinical features with frequencies of HLA‐B*27

Abstract: Ankylosing spondylitis (AS) is very often associated with human leukocyte antigen (HLA), particularly HLA-B*27. However, the strength of this association and clinical features may vary in different ethnic groups. Our study aims to assess the distribution of HLA-A, -B, -Cw and DRB1 alleles in Moroccan patients with AS and to compare the clinical features of AS and the frequencies of HLA-B27 in patients from Morocco with other series. Seventy-five patients diagnosed with AS and assessed for clinical manifestatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 47 publications
0
7
1
Order By: Relevance
“…We could not confirm some other associations described in smaller AS or SpA cohorts elsewhere32–34 perhaps due to clinical heterogeneity. One small recent study of HLA-A, HLA-B, HLA-C and DRB1 alleles in 75 Moroccan patients with AS reported an allele frequency of HLA-B*27 of 32%, with associations also seen with B*57 , C*02 and DRB1*15 and negative associations with HLA-B*35 and B*49 32. The reasons for the discrepancies of these data and ours are hard to interpret given the small size of the cohort, which precluded examination of HLA-B*27 negatives.…”
Section: Discussioncontrasting
confidence: 56%
“…We could not confirm some other associations described in smaller AS or SpA cohorts elsewhere32–34 perhaps due to clinical heterogeneity. One small recent study of HLA-A, HLA-B, HLA-C and DRB1 alleles in 75 Moroccan patients with AS reported an allele frequency of HLA-B*27 of 32%, with associations also seen with B*57 , C*02 and DRB1*15 and negative associations with HLA-B*35 and B*49 32. The reasons for the discrepancies of these data and ours are hard to interpret given the small size of the cohort, which precluded examination of HLA-B*27 negatives.…”
Section: Discussioncontrasting
confidence: 56%
“…Alleles B*35 and B*51 high frequency was like Lak population, whereas B*15 is low frequent in Lak population. The allele frequency of B*27 – which is associated with Ankylosing spondylitis [45] – is low frequent in Lak population as other populations so. In Africans, alleles B*35 and B*53 were high frequent [46] as the Laks respectively are and are not so.…”
Section: Discussionmentioning
confidence: 86%
“…Reveille et al found that the frequency of HLA‐C*02 was increased in white AS patients 8 . In a study of Macedonian and Moroccan AS populations, HLA‐C*02 was found to be positively correlated with the occurrence of AS 30,31 . HLA‐C*12:02 has been confirmed to be closely related to late‐onset psoriasis in the Japanese population.…”
Section: Discussionmentioning
confidence: 97%